Consuming Africa: safari aesthetics in the Johannesburg beauty industry. Issue 1 (2nd January 2022) - Falkof, Nicky
ABSTRACT: This article considers the way in which high-end beauty services in Johannesburg use a particular notion of "Africa" to brand themselves. Globally, the beauty industry is designed around an idea of indulgence, with pampering posited as a means of self-care, survival and joy. Marketing for beauty destinations often draws on an Orientalist idea of the "mysterious east, " invoking the stereotyped serenity of locations like Bali to offer bite-sized consumable contentment to clients. While it retains this focus on self-care as a practice of happiness, the burgeoning luxury industry in South Africa has seen the development of a new local aesthetic that treats the continent as an exotic landscape filled with healing plants and local wisdom. The article analyses the websites and physical salons of three high-end Johannesburg spas order to discuss their visual and textual representations of a mythic Africa as a site for luxury, indulgence and post-feminist self-care.